SIMILARITY AND DIFFERENCES ASPECTS OF GRADUONIMIC SERIES FORMED BY SEMANTIC CATEGORIES OF VERBS IN UZBEK AND ENGLISH LANGUAGES - Otaboyeva Mazmuna Rahimovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article is presented as an example of research on the study of the graduonymy of verbs in the Uzbek and English languages, and the similar and different aspects of the graduonymy series formed according to the semantic categories of the verbs in the languages being compared. cited. Also, in the article, the semantic categories of verbs of action, verbs of speech, verbs of state, verbs of thought, action verbs of result in Uzbek and verbs of action, verbs of thought, verbs of reason in English Verbs were separated into semantic groups such as verbs, verbs of the state of occurrence, aspect verbs, and the verbs were analyzed from the explanatory dictionaries, and graduonimic lines were created with the participation of their synonyms and opposite meanings.